Chronic pain and weight regain in a lifestyle modification trial. (1st January 2021) - Goessl, Cody L.; Befort, Christie A.; Pathak, Ram D.; Ellerbeck, Edward F.; VanWormer, Jeffrey J.
Abstract: Objective: Obesity and chronic pain often co‐occur and exert bidirectional influences on one another. How patients with obesity and chronic pain respond to weight loss treatments, however, remains unclear. This study evaluated body weight, physical activity, and diet outcomes in participants with and without chronic pain in a 2‐year behavioral weight loss trial. Methods: An analytical cohort of 397 adults was assembled from a Midwestern healthcare system that participated in the larger trial. Participants with chronic pain 1 year prior to, or during, the trial were identified using a validated medical records algorithm. Mixed models were used to estimate changes in outcomes over 24 months. Results: One‐third of participants ( n  = 130) had chronic pain. After adjustment for age, sex, body mass index, and trial arm, weight loss was similar in both groups at 6‐months (−7.0 ± 0.8 kg with chronic pain vs. −7.7 ± 0.6 kg without). Participants with chronic pain had significantly less weight loss at 24‐months relative to those without (−3.6 ± 0.5 vs. −5.2 ± 0.4 kg; p  = 0.007). Physical activity, screen time, dietary fat, fruit/vegetable consumption, and sugar‐sweetened beverage intake improved similarly in both groups over time. Conclusions: Participants with chronic pain lost ∼33% less weight over 2 years, which was driven by greater weight regain after the first 6 months. Future research should test tailored weight loss maintenance strategies for individuals with chronic pain.